Study of the transfer mechanism of intangible assets in the region - O. V. Opyatova (Вестник Северо-Кавказского федерального университета, 2022)
The most important criterion for the effectiveness of the transfer of intangible assets is the implementation of research results in the activities of the economic entity, but in the regions the transfer mechanism is ineffective. It is necessary to develop recommendations on the creation, organization and functioning of innovation transfer centers, identifying the real needs of enterprises of a given region in innovative developments through market research, activate the activity of producers and consumers to implement innovations and turn their results into a real product. Comprehensive measures will contribute to strengthening the position of the region, the active development of research potential of the region.